Antifungal Activity of Beluntas “Indian Camphorweed” (Pluchea indica) Ethanol Extract on Candida albicans In Vitro Using Different Solvent Concentrations - Demolsky, Wayan Larissa; Sugiaman, Vinna Kurniawati; Pranata, Natallia (European Journal of Dentistry, 2021)
Objective Oral candidiasis is an infection caused by pathogenic fungi Candida albicans, with a considerably high prevalence of 20 to 72%. Indian camphorweed (Pluchea indica) also known as “beluntas” as the local name has been known as a traditional medicine in Indonesia. The objective of this study is to research the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) of beluntas ethanolic extract against the growth of C. albicans.Materials and Methods The MIC and MFC were measured by microdilution assay and total plate count respectively with a variation of solvents (DMSO 1%, 10%, and 4%) and beluntas extract with concentrations between 0.3125 and 200 mg/mL. Amphotericin and nystatin were used as a comparison.Statistical Analysis One-way analysis of variance and posthoc Tukey test were used to determine the significant difference between treatments.Results It was found that the MIC ranged from 50 to 200 mg/mL in the test with DMSO 10% solvent and MFC was found to be at a concentration of 200 mg/mL. However, there is a significant inhibitory effect and killing effect from DMSO 10% against C. albicans (p = 0.000). MIC was also found within concentrations of 100 mg/mL of beluntas extract in DMSO 4%. In this study, the DMSO 4% concentration neither showed significant inhibitory effects nor killing effects; therefore, the result was acceptable (p = 0.357).Conclusion Ethanol extract of beluntas (P. Indica) has the potential of being an antifungal agent with inhibitory activity in concentrations ≥100 mg/mL, which is similar to nystatin (p = 0.278). The MFC for the extract was above 100 mg/mL, which cannot be measured with this method as a higher concentration of DMSO is needed, which had a toxic effect on the tested fungi.
Keywords: Candida albicans; nystatin; amphotericin B; Indian camphorweed; Pluchea indica; beluntas